The processes of the catalytic cycle of the cytochrome system associated with its activation by means of the enzyme Nicotinamide-β-adenine dinucleotide phosphate-H-ferrihemoprotein oxidoreductase - Popova Olga; Bylinskaya Daria; Nikitina Anastasia; Ukrainskaya Olga (BIO Web of Conferences)
The paper presents a theoretical study of the molecular mechanism of activation of the cytochrome P450 system by the enzyme Nicotinamide-β-adenine dinucleotide phosphate-H-ferrihemoprotein oxidoreductase in the catalytic cycle. The relevance of studying cytochrome P450 enzymes and their activator is determined by the development of methods for effective diagnostics of hepatobiliary pathologies. It was found that the enzyme Nicotinamide-β-adenine dinucleotide phosphate-H-ferrihemoprotein oxidoreductase functions as a redox “partner” for cytochromes P450. An electrochemical method used to study the monooxygenase system of microsomal oxidation is described. Proposals for further study of the cytochrome system, as well as the possibility of their application in practice are put forward. This is of particular interest to veterinary pharmacology, which is dictated by the trend towards an increase in the use of drugs, as well as the deterioration of environmental conditions in general.